ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI TELUR PUYUH DI GAMPONG GEUNTENG KECAMATAN MEURAH DUA KABUPATEN PIDIE JAYA - Safrika Safrika; Hamdani Hamdani (Universitas Galuh Ciamis, 2021)
Quail is one type of poultry that has the potential to be developed and increased production. The high market demand at this time provides an opportunity for quail egg farmers in Gampong Geunteng, Meurah Dua District, Pidie Jaya Regency to increase quail egg production. Lack of production is a problem for farmers because it has an impact on the lack of efforts to meet market demand. This study aims to determine the factors that influence the production of quail eggs in Geunteng Village, Meurah Dua District, Pidie Jaya Regency. The research design used is quantitative and qualitative. This research uses multiple linear regression analysis method. The results showed that the revenue of the quail egg business in Gampong Geunteng, Meurah Dua District, Pidie Jaya Regency was Rp. 351,920,000 per business period. Based on the results of data analysis shows that the amount of feed and labor affect the production of quail eggs.